COMPARATIVE CFD ANALYSIS OF CONVENTIONAL AND MODIFIED SOLAR STILLS - Sharma, Priyanka; Birla, Shyam Kumar (International Journal of Research -GRANTHAALAYAH, 2022)
This research presents a comparative analysis between a conventional solar still and a modified version to determine the most efficient design for freshwater production. Computational Fluid Dynamics (CFD) simulations were carried out using ANSYS FLUENT to analyse the heat and mass transfer processes occurring within the solar stills. A single-slope solar still configuration was modelled for both setups, and key performance parameters were evaluated. The results aim to provide a deeper understanding of the thermal behaviour and effectiveness of design modifications, offering practical guidance for the development of high-efficiency solar desalination systems.